Phonological awareness intervention on reading fluency in children with suspected learning disorders - Radiya Shifa Nevin; Restu Wahyu Wibawati; Nadya Susanti (Himpunan Pengembang Kurikulum Indonesia, 2026)
This study discusses the effect of phonological awareness intervention, especially phoneme blending, on the reading fluency of 3rd grade elementary school children with suspected learning disorders in Surakarta. This study aims to determine whether there is an effect of phonological awareness intervention on the reading fluency of children suspected of having learning disorders in grade 3 of elementary school in Surakarta. This research is a quantitative research using the One Group Pre-Test and Post-Test Design method and non-parametric statistical analysis using the Wilcoxon Signed Ranks Test with a total frequency of interventions of 8 treatments. The number of samples used in this study was 10 children with suspected learning disorders in grade 3 of elementary school in Surakarta. The results of this study indicate that based on the results of non-parametric statistical analysis using the Wilcoxon Signed Ranks Test obtained a significance value of p = 0.005. Because the p value < 0.05, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a statistically significant difference between WCPM scores in the pretest and posttest. The results of the study show that PA intervention on reading fluency is influenced by consistency of the intervention implementation. Abstrak Penelitian ini membahas mengenai pengaruh intervensi phonological awareness khususnya phonem blending terhadap kemampuan kelancaran membaca anak kelas 3 SD dengan suspek gangguan belajar di Surakarta. Penelitian ini memiliki tujuan untuk mengetahui pengaruh intervensi phonological awareness terhadap reading fluency anak suspek gangguan belajar kelas 3 SD di Surakarta serta mengetahui kemampuan reading fluency anak dengan suspek gangguan belajar kelas 3 SD sebelum dan setelah diberikan intervensi phonological awareness. Penelitian dengan pendekatan kuantitatif ini menggunakan metode One Group Pre-Test and Post-Test Design dan uji analisis stastistik non-parametrik menggunakan Wilcoxon Signed Ranks Test dengan jumlah frekuensi intervensi sebanyak 8 kali perlakuan. Jumlah sampel yang digunakan dalam penelitian ini adalah 10 anak dengan suspek gangguan belajar kelas 3 SD di Surakarta. Hasil penelitian ini menunjukkan bahwa berdasarkan hasil analisis stastistik non-parametrik menggunakan Wilcoxon Signed Ranks Test memperoleh nilai signifikansi p=0.005. Karena nilai p < 0.05, maka hipotesis nol (Ho) ditolak dan hipotesis alternatif (Ha) diterima. Hal ini membuktikan adanya perbedaan signifikan secara statistik antara skor WCPM pada pretest dan posttest. Hasil penelitian menunjukkan bahwa intervensi phonological awareness terhadap reading fluency dipengaruhi oleh kemampuan awal anak dan konsistensi pelaksanaan intervensi. Kata Kunci: phonem blending; phonological awareness; reading fluency